Viscosity measurement of FeO–SiO2–V2O3–TiO2 slags in the temperature range of 1644–1791 K and modelling by using ion-oxygen parameter. (9th August 2018) - Liu, Shiyuan; Wang, Lijun; Chou, Kuo-chih
ABSTRACT: The viscosity of the FeO–SiO2 –TiO2 –V2 O3 system with TiO2 between 5 and 15-mass %, V2 O3 between 5 and 15-mass% and FeO/SiO2 mass ratio between 1.4 and 2.2 was measured at temperature 1644–1791 K. It was found that the viscosity of slag increased with increasing V2 O3 level, decreased with increasing temperature and FeO/SiO2 ratio, and decreased with increasing TiO2 content. The viscosity values of FeO–SiO2 –V2 O3 –TiO2 system were calculated by employing various viscosity models. The mean deviations are about 54.04, 84.13, 18.96, and 4.48% for the values by Mill, modified Riboud, and, respectively. Thus, a model based on the ion-oxygen parameter, which can describe the influence of components and temperature, provided the best fit to the viscosity data. There were three kinds of crystalline phases, Fe2 SiO4, Fe2 TiO4, and FeV2 O4 in all samples. The SiO2 crystal appeared in Al, Al3, and B3 samples.